A silicon-based composite gel gasket with high thermal conductivity and low thermal resistance and a preparation method thereof

CN122978729APending Publication Date: 2026-10-27WUXI JIYUAN SEMICONDUCTOR MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611246558.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]为了改善上述问题,减少相关技术中凝胶垫片导热性差、热阻低、力学性能差的问题,本发明特提供一种高导热低热阻的硅基复合凝胶垫片及其制备方法,以解决上述背景技术中提出的问题

Benefits of technology

1、本发明通过二元粒径球形氧化铝密堆积搭配六方氮化硼纳米片与碳化硅晶须构建多尺度声子传导通路,配合硅烷偶联剂界面改性强化填料与硅氧烷基体的结合强度,减少界面声子散射损耗,得到更高的本征导热系数,提升垫片导热性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1786956498230-000007
    Figure REF-OBJ-1786956498230-000007
  • Figure REF-OBJ-1786956498230-000010
    Figure REF-OBJ-1786956498230-000010
  • Figure DH9WLANWKOAHP4WQAUBSINSTIWUIA9NDMHQOGGPY
    Figure DH9WLANWKOAHP4WQAUBSINSTIWUIA9NDMHQOGGPY
Patent Text Reader

Abstract

The application discloses a silicon-based composite gel gasket with high thermal conductivity and low thermal resistance and a preparation method thereof, and particularly relates to the technical field of new chemical materials, and relates to a silicon-based composite gel gasket with high thermal conductivity and low thermal resistance and a preparation method thereof. The silicon-based composite gel gasket with high thermal conductivity and low thermal resistance is prepared from 9-15 parts of hydrogen-containing polydimethylsiloxane, 3-7 parts of fluorine-containing hydrogen-containing polysiloxane, 59-73 parts of dimethyl silicone oil, 15-25 parts of base glue, 0.15-0.2 parts of 1-ethynylcyclohexanol inhibitor and 1000 parts of base glue component. The application constructs a multi-scale phonon conduction path by densely packing binary particle size spherical alumina with hexagonal boron nitride nanosheets and silicon carbide whiskers, strengthens the bonding strength of the filler and the siloxane matrix by means of interface modification of the silane coupling agent, reduces the interface phonon scattering loss, and obtains a higher intrinsic thermal conductivity, so that the thermal conductivity of the gasket is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new chemical materials technology, and more specifically, to a silicon-based composite gel pad with high thermal conductivity and low thermal resistance and its preparation method. Background Technology

[0002] With the continuous increase in power density of electronic components, the heat generation is also increasing daily, placing higher demands on the thermal conductivity and interfacial thermal resistance of thermal pads in thermal management systems. Gel pads are viscoelastic sheet-like thermally conductive interfacial materials, mainly used to fill the microscopic gaps between electronic components and heat sinks, expel interfacial air, and establish efficient heat conduction pathways. Compared with traditional thermally conductive silicone pads, gel pads have the characteristics of low modulus, low stress, and high compressibility, and can fully adhere to rough surfaces under lower assembly pressure, reducing thermal resistance caused by insufficient interfacial contact. Therefore, the development of a new type of composite gel pad has significant application value.

[0003] Currently, silicone-based gel gaskets in related technologies typically include acrylate monomers, acrylate crosslinking agents, free radical initiators, non-reactive plasticizers, and thermally conductive fillers. Among them, acrylate monomers serve as polymerizable basic components, providing a flexible network framework after curing; acrylate crosslinking agents are used to introduce chemical crosslinking points between polymer chains, giving the gasket shape stability and a certain degree of elasticity; free radical initiators are used to initiate monomer polymerization and crosslinking reactions; non-reactive plasticizers are used to reduce the matrix modulus and improve flexibility; and thermally conductive fillers impart thermal conductivity to the material.

[0004] However, in practical use, it still has some drawbacks, such as poor thermal conductivity. The acrylate or polyurethane backbone of traditional gel gaskets is composed of carbon-carbon or carbon-oxygen single bonds. There are only weak van der Waals forces between molecular chains, but no low internal rotation barrier like that of siloxane backbones, resulting in severe scattering during phonon transport. It also has low thermal resistance. The polymer matrix of traditional gel gaskets has a large modulus and insufficient flexibility. Under low assembly pressure, it cannot generate sufficient elastic or plastic deformation to conform to the micron-level rough peaks and valleys at the interface, resulting in a small actual contact area and a large number of micro-nano air gaps remaining between the interfaces. Furthermore, it has poor mechanical properties. The cross-linking network density of traditional gel gaskets is low and the physical entanglement between molecular chains is weak, resulting in insufficient tensile strength and tear resistance. Under long-term cyclic compression conditions, it is prone to permanent deformation and stress relaxation, and the sealing surface fit continues to decline, eventually leading to sealing failure and media leakage. Summary of the Invention

[0005] To improve the above-mentioned problems and reduce the issues of poor thermal conductivity, low thermal resistance, and poor mechanical properties of gel pads in related technologies, this invention provides a silicon-based composite gel pad with high thermal conductivity and low thermal resistance and its preparation method, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A silicon-based composite gel pad with high thermal conductivity and low thermal resistance and its preparation method, comprising the following steps: S1. Add hydrogen-containing polydimethylsiloxane, fluorinated hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir at room temperature and speed of 70-110 r / min for 20-30 min, and then degas at -0.09 MPa vacuum for 10 min to obtain curing agent components. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled drying oven, control the oxygen content in the oven to be below 500ppm, and carry out a two-stage vulcanization treatment at 150-160℃ for 2-3 hours. After naturally cooling to room temperature, transfer it to a constant temperature and humidity environment at 20-30℃ and 45-55% for 8-16 hours of static curing. Trim and trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0007] Preferably, the raw materials for preparing the high thermal conductivity and low thermal resistance silicone-based composite gel pad include: 9-15 parts of hydrogen-containing polydimethylsiloxane, 3-7 parts of fluorinated hydrogen-containing polysiloxane, 59-73 parts of dimethyl silicone oil, 15-25 parts of base adhesive, 0.15-0.2 parts of 1-ethynylcyclohexanol inhibitor, and 1000 parts of base adhesive component.

[0008] Preferably, the preparation method of the base adhesive component includes the following steps: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 60-70℃ and 300-500 r / min for 2.5-3.5 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane are added to a polymerization reactor. Nitrogen gas is introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent are added. The mixture is stirred at 105-115℃ and 70-90 r / min for 3.5-4.5 h until ring-opening equilibrium is reached. The temperature is first increased to 130℃ at a gradient rate of 2℃ / min and held for 1 h to decompose the catalyst. The temperature is then increased to 150℃. Low-boiling substances are first pre-removed under a vacuum of -0.05MPa for 30 min. The vacuum is then gradually increased to -0.095MPa and maintained for 2 h. A small amount of nitrogen gas is introduced throughout the process. After the devolatilization is completed, heating is stopped, and the mixture is cooled to room temperature and discharged to obtain the base adhesive. C4. Raw methyl vinyl silicone rubber and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 95-105℃ for 3-8 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0009] Preferably, the raw materials for preparing the base adhesive component and their weight parts are as follows: 100 parts base adhesive, 8-18 parts vinyl MQ silicone resin, 10-22 parts methyl phenyl silicone oil, 5-12 parts liquid fluorosilicone rubber, 6-15 parts pre-dispersed thermally conductive micro powder, 4-9 parts vinyl fluorosilicone oil, 45-72 parts thermally conductive filler paste, 190-232 parts modified thermally conductive filler, and 0.8-1 parts platinum catalyst.

[0010] Preferably, the silane coupling agent hydrolysate is obtained by mixing vinyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of 6:2:1.5:0.5.

[0011] Preferably, the modified thermally conductive filler is prepared from spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and hydrolysate of silane coupling agent in a mass ratio of 2-4:6-8:0.18-2.25.

[0012] Preferably, the thermally conductive filler paste is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 28.8-31.5:4.5-7.2:0.9-1.08:12.6-16.2:2.89-4.32.

[0013] Preferably, the base adhesive is prepared from octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 65-72:22-24:4-13:0.05:0.6-0.75.

[0014] Preferably, the pre-dispersed thermally conductive micropowder is prepared from methyl vinyl silicone rubber raw rubber, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and pre-diluted complex in a mass ratio of 100:40-90:1.2-1.7:0.06-0.1.

[0015] Preferably, the pre-diluted complex is obtained by diluting a platinum-divinyltetramethyldisiloxane complex with a base adhesive obtained from C3 at a mass ratio of 10:1.

[0016] The technical effects and advantages of this invention are as follows: 1. This invention constructs a multi-scale phonon conduction pathway by densely packing binary spherical alumina particles with hexagonal boron nitride nanosheets and silicon carbide whiskers, and strengthens the bonding strength between the filler and the siloxane matrix by interfacial modification with silane coupling agent, thereby reducing interfacial phonon scattering loss and obtaining a higher intrinsic thermal conductivity, thus improving the thermal conductivity of the gasket. 2. This invention controls the crosslinking density and overall flexible deformation capability of the pre-dispersed thermally conductive micropowder system, and reduces internal micropores and interface structural defects by combining it with the filler dispersion system, thereby improving the interface adhesion to eliminate air gaps between interfaces and obtaining lower interface contact thermal resistance and total thermal resistance. 3. This invention constructs a uniform and stable three-dimensional cross-linked network by combining rigid resin reinforcement with partially cross-linked micro powder for synergistic toughening, optimizes stress transmission and dispersion mechanisms, improves the tensile strength and resistance to permanent compression deformation of the gasket, alleviates performance degradation under long-term cyclic loading, and enhances mechanical properties. 4. This invention provides migratable low-energy segments through the synergistic effect of a ternary copolymer fluorinated matrix and a fluorinated crosslinking agent. Under the high temperature of the two-stage vulcanization, the fluorinated segments are spontaneously enriched on the surface and anchored in the crosslinking network to form a stable gradient low-energy structure, resulting in a lower surface energy. Detailed Implementation

[0017] The present invention will be further described in detail below with reference to the embodiments of the present invention. Unless otherwise specified below, the raw materials used in the various examples and embodiments of the present invention are all commercially available common materials. Preparation Examples 1-5 A base adhesive component, the components and their corresponding proportions of which are shown in the table below, is prepared using the following method: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 65℃ and 400 r / min for 3 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. The silane coupling agent hydrolysate is prepared by mixing vinyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of 6:2:1.5:0.5. The modified thermally conductive filler was prepared by mixing spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and hydrolysate of silane coupling agent in a mass ratio of 3:7:0.2. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. The silane coupling agent hydrolysate is prepared by mixing vinyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of 6:2:1.5:0.5. The thermally conductive filler paste is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 30:6:0.9:14.4:3.6. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 110°C and 80 r / min for 4 hours until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 hour to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 minutes. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 hours. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. The base adhesive is prepared by mixing octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 69:23:8:0.05:0.7. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 100℃ for 5 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. The vinyl content of the raw methyl vinyl silicone rubber is 0.15 mmol / g; The hydrogen content of the hydrogen-containing silicone oil is 0.5% by mass. The pre-diluted complex was obtained by diluting the platinum-divinyltetramethyldisiloxane complex with the base adhesive obtained from C3 at a mass ratio of 10:1. The pre-dispersed thermally conductive micropowder was prepared from methyl vinyl silicone rubber raw material, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and pre-diluted complex in a mass ratio of 100:60:1.6:0.08. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0018] Specifically, the vinyl MQ silicone resin is a vinyl fluorinated MQ silicone resin with a vinyl content of 1.0 mmol / g; The methylphenyl silicone oil has a phenyl molar content of 15% and a viscosity of 350 mPa·s at 25°C. Specifically, the liquid fluorosilicone rubber is a vinyl-terminated liquid fluorosilicone rubber with a vinyl content of 0.25 mmol / g; Specifically, the vinyl fluorosilicone oil is vinyl-terminated polytrifluoropropylmethylsiloxane with a vinyl content of 0.20 mmol / g; The platinum catalyst is specifically a platinum-vinylsiloxane complex catalyst with a platinum content of 3000 ppm. Table: Components and their mass ratios (kg) of the raw materials used in Preparation Examples 1-5

[0019] Preparation Example 6 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 60℃ and 300 r / min for 2.5 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 110°C and 80 r / min for 4 hours until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 hour to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 minutes. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 hours. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 100℃ for 5 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0020] Preparation Example 7 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 70℃ and 500 r / min for 3.5 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 110°C and 80 r / min for 4 hours until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 hour to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 minutes. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 hours. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 100℃ for 5 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0021] Preparation Example 8 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 65℃ and 400 r / min for 3 h after the reaction was completed. After centrifugation, the mixture was washed twice with anhydrous ethanol and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 105℃ and 70 r / min for 3.5 h until ring-opening equilibrium was reached. The temperature was first increased to 130℃ at a gradient rate of 2℃ / min and held for 1 h to decompose the catalyst. The temperature was then increased to 150℃. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 min. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 h. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 100℃ for 5 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0022] Preparation Example 9 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 65℃ and 400 r / min for 3 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 115°C and 90 r / min for 4.5 h until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 h to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first pre-removed under a vacuum of -0.05 MPa for 30 min. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 h. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 100℃ for 5 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0023] Preparation Example 10 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 65℃ and 400 r / min for 3 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 110°C and 80 r / min for 4 hours until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 hour to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 minutes. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 hours. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 95℃ for 3 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0024] Preparation Example 11 One base adhesive component differs from that in Preparation Example 1 in that its preparation method is as follows: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 65℃ and 400 r / min for 3 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane were added to a polymerization reactor. Nitrogen gas was introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent were added. The mixture was stirred at 110°C and 80 r / min for 4 hours until ring-opening equilibrium was reached. The temperature was first increased to 130°C at a gradient rate of 2°C / min and held for 1 hour to decompose the catalyst. The temperature was then increased to 150°C. Low-boiling substances were first removed under a vacuum of -0.05 MPa for 30 minutes. The vacuum was then gradually increased to -0.095 MPa and maintained for 2 hours. A small amount of nitrogen gas was introduced throughout the process. After the devolatilization was completed, heating was stopped, and the mixture was cooled to room temperature and discharged to obtain the base adhesive. C4. Methyl vinyl silicone rubber raw material and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 105℃ for 8 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

[0025] Preparation Example 12 One base adhesive component differs from Preparation Example 1 in that the modified thermally conductive filler is prepared from spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and hydrolysate of silane coupling agent in a mass ratio of 2:8:0.18.

[0026] Preparation Example 13 One base adhesive component differs from Preparation Example 1 in that the modified thermally conductive filler is prepared from spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and hydrolysate of silane coupling agent in a mass ratio of 4:6:0.25.

[0027] Preparation Example 14 One base adhesive component differs from Preparation Example 1 in that the thermally conductive filler paste is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 31.5:4.5:0.9:12.6:2.89.

[0028] Preparation Example 15 One base adhesive component differs from Preparation Example 1 in that the thermally conductive filler paste is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 28.8:7.2:1.08:16.2:4.32.

[0029] Preparation Example 16 One base adhesive component differs from Preparation Example 1 in that the base adhesive is prepared from octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 72:24:4:0.05:0.6.

[0030] Preparation Example 17 One base adhesive component differs from Preparation Example 1 in that the base adhesive is prepared from octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 65:22:13:0.05:0.75.

[0031] Preparation Example 18 One base component differs from Preparation Example 1 in that the pre-dispersed thermally conductive micropowder is prepared from methyl vinyl silicone rubber raw rubber, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and a pre-diluted complex in a mass ratio of 100:90:1.7:0.10.

[0032] Preparation Example 19 One base component differs from Preparation Example 1 in that the pre-dispersed thermally conductive micropowder is prepared from methyl vinyl silicone rubber raw rubber, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and a pre-diluted complex in a mass ratio of 100:40:1.2:0.06.

[0033] Preparation Examples 20-24 A high thermal conductivity and low thermal resistance silicon-based composite gel pad is prepared by the following method, and its components and their corresponding proportions are shown in the table below. S1. Add hydrogen-containing polydimethylsiloxane, fluorinated hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir for 25 min at room temperature and 90 r / min, and then degas at -0.09 MPa vacuum for 10 min to obtain the curing agent component. The base adhesive was prepared from Preparation Example 1; The active hydrogen mass fraction of the hydrogen-containing polydimethylsiloxane is 0.45%. The trifluoropropyl molar content of the fluorinated hydrogen-containing polysiloxane is 35%, and the active hydrogen mass fraction is 0.4%. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. The base adhesive component was prepared in Preparation Example 1; S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled forced-air drying oven, control the oxygen content in the oven to be below 500ppm, and perform a two-stage vulcanization treatment at 155℃ for 2.5h. After naturally cooling to room temperature, transfer it to a constant temperature and humidity environment of 25℃ and 50% relative humidity for 12h to stand and mature. Trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0034] Table: Components and their mass ratios (kg) of the raw materials used in Preparation Examples 10-14

[0035] Preparation Example 25 A silicon-based composite gel pad with high thermal conductivity and low thermal resistance differs from preparation example 20 in that its preparation method is as follows: S1. Add hydrogen-containing polydimethylsiloxane, fluorine-containing hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir for 20 min at room temperature and 70 r / min, and then degas at -0.09 MPa vacuum for 10 min to obtain the curing agent component. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled forced-air drying oven, control the oxygen content in the oven to be below 500ppm, and perform a two-stage vulcanization treatment at 155℃ for 2.5h. After naturally cooling to room temperature, transfer it to a constant temperature and humidity environment of 25℃ and 50% relative humidity for 12h to stand and mature. Trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0036] Preparation Example 26 A silicon-based composite gel pad with high thermal conductivity and low thermal resistance differs from that in Preparation Example 10 in that its preparation method is as follows: S1. Add hydrogen-containing polydimethylsiloxane, fluorine-containing hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir for 30 min at room temperature and 110 r / min, and then degas at -0.09 MPa vacuum for 10 min to obtain the curing agent component. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled forced-air drying oven, control the oxygen content in the oven to be below 500ppm, and perform a two-stage vulcanization treatment at 155℃ for 2.5h. After naturally cooling to room temperature, transfer it to a constant temperature and humidity environment of 25℃ and 50% relative humidity for 12h to stand and mature. Trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0037] Preparation Example 27 A silicon-based composite gel pad with high thermal conductivity and low thermal resistance differs from that in Preparation Example 10 in that its preparation method is as follows: S1. Add hydrogen-containing polydimethylsiloxane, fluorinated hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir for 25 min at room temperature and 90 r / min, and then degas at -0.09 MPa vacuum for 10 min to obtain the curing agent component. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled drying oven, control the oxygen content in the oven to be below 500ppm, perform a two-stage vulcanization treatment at 150℃ for 2h, and after naturally cooling to room temperature, transfer it into a constant temperature and humidity environment at 20℃ and 45% relative humidity for 8h of static curing, cut and trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0038] Preparation Example 28 A silicon-based composite gel pad with high thermal conductivity and low thermal resistance differs from that in Preparation Example 10 in that its preparation method is as follows: S1. Add hydrogen-containing polydimethylsiloxane, fluorinated hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir for 25 min at room temperature and 90 r / min, and then degas at -0.09 MPa vacuum for 10 min to obtain the curing agent component. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled forced-air drying oven, control the oxygen content in the oven to be below 500ppm, perform a two-stage vulcanization treatment at 155℃ for 2.5h, let it cool naturally to room temperature, and then transfer it to a constant temperature and humidity environment of 30℃ and 55% relative humidity for 16h to stand and mature. Trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.

[0039] Preparation Examples 29-46 A high thermal conductivity and low thermal resistance silicon-based composite gel pad differs from Preparation Example 20 in that the base adhesive component and the use of the base adhesive are different, and the specific correspondence is shown in the table below.

[0040] Table: Comparison of Base Rubber Components and Base Rubber Usage in Preparation Examples 29-46

[0041] Performance testing High thermal conductivity and low thermal resistance silicon-based composite gel pads prepared in each preparation example were selected for testing. The test subjects were 270 high thermal conductivity and low thermal resistance silicon-based composite gel pads, with 10 pads in each group. Their thermal conductivity, thermal resistance, and mechanical properties were tested. The specific testing steps are as follows: Thermal conductivity: First, samples of the high thermal conductivity and low thermal resistance silicon-based composite gel pads prepared in the preparation example were taken. Circular samples with a diameter thermal resistance of 30 mm and a thickness thermal resistance of 1.0 mm were cut. A steady-state heat flow method thermal conductivity tester was used to test the thermal conductivity of the samples under conditions of a test pressure thermal resistance of 0.05 MPa, a hot-cold surface temperature difference thermal resistance of 10 °C, and an ambient temperature thermal resistance of 25 °C. The thermal conductivity of the samples was obtained to characterize the thermal conductivity of the high thermal conductivity and low thermal resistance silicon-based composite gel pads. The test results and evaluation criteria are as follows: Thermal conductivity ≥ 3.5 W / (m·K) (considered as high thermal conductivity); Thermal conductivity < 3.5 W / (m·K) (considered as poor thermal conductivity).

[0042] Thermal resistance: First, a sample of the high thermal conductivity and low thermal resistance silicon-based composite gel pad prepared in the preparation example was taken, and a 25 mm area was cut off. Square samples with a thickness of 1.0 mm were tested using a steady-state thermal resistance tester at an assembly pressure of 0.07 MPa and a test temperature of 25°C. The interfacial contact thermal resistance was calculated by subtracting the sample body thermal resistance from the total thermal resistance, thus characterizing the thermal resistance of the high thermal conductivity and low thermal resistance silicon-based composite gel gasket. The test results and evaluation criteria are as follows: Interfacial contact thermal resistance ≤0.50 (Considered as having low thermal resistance); Interfacial contact thermal resistance > 0.50 (Considered as having high thermal resistance).

[0043] Mechanical properties: First, samples of the high thermal conductivity and low thermal resistance silicon-based composite gel gasket prepared in the preparation example were taken. Flat, dumbbell-shaped specimens conforming to national standards (Type I) were cut and subjected to tensile tests at a constant speed of 500 mm / min under constant temperature and humidity conditions (25℃, 50% relative humidity). The tensile strength of the specimens was tested, and the average tensile strength of parallel specimens was calculated to characterize the mechanical properties of the high thermal conductivity and low thermal resistance silicon-based composite gel gasket. The test results and evaluation criteria are as follows: Tensile strength ≥ 1.0 MPa (considered as having strong mechanical properties); 0.8MPa < tensile strength < 1.0MPa (considered as having average mechanical properties); Tensile strength ≤ 0.8 MPa (considered as having weak mechanical properties).

[0044] It should be specifically noted that the high thermal conductivity and low thermal resistance silicon-based composite gel pads obtained above are produced under normal production methods. Any defective high thermal conductivity and low thermal resistance silicon-based composite gel pads produced are disregarded.

[0045] Examples 1-9

[0046] The corresponding relationship of the preparation methods used for a high thermal conductivity and low thermal resistance silicon-based composite gel pad is shown in the table below.

[0047] Table: Comparison of the application of high thermal conductivity and low thermal resistance silicon-based composite gel pads in Examples 1-9

[0048] Extract the high thermal conductivity and low thermal resistance silicon-based composite gel pads from Examples 1-9 above, and test their thermal conductivity, interfacial contact thermal resistance and tensile strength according to the above measurement steps and standards. The average value of the test results is recorded in the table below.

[0049] Table: Performance test results of thermal conductivity, interfacial contact thermal resistance and tensile strength in Examples 1-9

[0050] As can be seen from the table above, the preparation process of the high thermal conductivity and low thermal resistance silicon-based composite gel pads in Examples 1-9 all effectively improves the production effect of high thermal conductivity and low thermal resistance silicon-based composite gel pads. The base adhesive serves as a continuous phase matrix, and the introduction of fluorine units into the main chain strengthens the driving force of fluorine phase migration, providing a carrier for the crosslinking network and thermally conductive filler. The modified thermally conductive filler serves as the core thermally conductive phase, and the use of binary particle size distribution increases the packing density, constructing a continuous bulk thermally conductive pathway and improving the characteristic thermal conductivity of the samples. The hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers in the thermally conductive filler paste fill the micron-sized filler. Interfacial phonon bridging is constructed to reduce interfacial phonon scattering and further improve the thermal conductivity network. Silane coupling agent hydrolysate grafts reactive functional groups onto the filler surface, strengthening the interfacial bonding between the filler and siloxane matrix, eliminating interfacial voids, and reducing the filler-matrix interfacial thermal resistance. Vinyl MQ silicone resin participates in the crosslinking reaction, reinforcing the three-dimensional network structure and improving the gasket's resilience and resistance to compression deformation. Methyl phenyl silicone oil adjusts the system viscosity, improving the filler wetting effect and enhancing processing and dispersion uniformity. Liquid fluorosilicone rubber and vinyl fluorosilicone oil, as migratable low-energy components, spontaneously migrate to the matrix under high-temperature secondary vulcanization. The gasket surface is enriched, forming a gradient low-energy structure, which reduces the gasket's mechanical properties. Pre-dispersed thermally conductive micropowder contains pre-embedded thermally conductive pathways to maintain the system's low modulus characteristics, improve interfacial adhesion to reduce contact thermal resistance, and avoid the disruption effect of elasticity on the thermally conductive network. Hydrogen-containing polydimethylsiloxane and fluorinated hydrogen-containing polysiloxane are used as crosslinking agents to construct a complete crosslinked network through hydrosilylation, while the fluorinated crosslinking agent simultaneously replenishes migratable fluorine segments. A platinum catalyst catalyzes the hydrosilylation reaction, regulating the curing reaction rate. A 1-ethynylcyclohexanol inhibitor suppresses catalytic activity at room temperature, improving the storage capacity of the two-component system. Stability; Octamethylcyclotetrasiloxane and dimethylcyclosiloxane form the polymer backbone, providing the intrinsic flexibility and temperature resistance of siloxanes; trifluoropropylmethylcyclotrisiloxane introduces fluorine side chains, endowing the matrix with the intrinsic property of low mechanical properties; tetramethylammonium hydroxide silanolate catalyzes the ring-opening equilibrium polymerization of cyclosiloxanes; tetramethyldivinyldisiloxane acts as a capping agent to regulate the polymer molecular weight and vinyl functionality; methylvinyl silicone rubber raw rubber provides an elastic matrix for elastic micropowders, supporting thermally conductive fillers and ensuring the flexibility of micropowders; thus achieving the goal of improving the production effect of high thermal conductivity and low thermal resistance silicone-based composite gel gaskets; Its thermal conductivity is 4.2-4.8 W / (m·K), which is considered to be high thermal conductivity; the interfacial contact thermal resistance is 0.28-0.42. The tensile strength of Examples 1-3 and 5-9 is 1.15-1.65 MPa, which is considered to be high mechanical properties; the tensile strength of Example 4 is 0.95 MPa, which is considered to be low mechanical properties. It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that the silicone-based composite gel pad with the strongest thermal conductivity and low thermal resistance obtained by using 15 parts of hydrogen-containing polydimethylsiloxane, 5 parts of fluorinated hydrogen-containing polysiloxane, 65 parts of dimethyl silicone oil, 15 parts of base adhesive, 0.2 parts of 1-ethynylcyclohexanol inhibitor, and 1000 parts of base adhesive components exhibits the highest thermal conductivity. This is because a higher proportion of crosslinking agent allows for a more complete hydrosilylation reaction, resulting in a denser and more continuous three-dimensional crosslinked polymer network, reducing the matrix... The internal chain segment defects and free volume reduce the scattering loss of phonons in the siloxane matrix, improving the intrinsic thermal conductivity of the continuous phase. The higher crosslinking density accelerates the curing and shaping rate, effectively suppressing the gravitational settling and agglomeration drift of high-density thermally conductive fillers during the curing process. This results in a more uniform and stable arrangement of the multi-scale thermally conductive network constructed by binary alumina and nano-hybrid fillers, with better continuity and integrity of the thermal conduction pathway. The increased crosslinking degree increases the overall density of the gasket, reduces the presence of internal micropores and air gaps, eliminates the thermal resistance increment caused by the low thermal conductivity air phase, and further improves the heat conduction efficiency in the thickness direction of the gasket, as obtained from Examples 1-5.

[0051] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when preparing high thermal conductivity and low thermal resistance silicone-based composite gel pads, the pad prepared using 9 parts of hydrogen-containing polydimethylsiloxane, 3 parts of fluorinated hydrogen-containing polysiloxane, 73 parts of dimethyl silicone oil, 15 parts of base adhesive, 0.15 parts of 1-ethynylcyclohexanol inhibitor, and 1000 parts of the base adhesive component exhibits the lowest thermal resistance and the strongest mechanical properties. The reasons for this can be analyzed. The lower total amount of crosslinking agent keeps the crosslinking density of the system at a moderate level, the siloxane molecular chains retain sufficient degrees of freedom of movement, the overall modulus and hardness of the gasket are significantly reduced, the material softness and deformation compliance are greatly improved, and under the same assembly pressure, it can fully fill the micro-uneven morphology of the heat dissipation interface, effectively eliminate the air gap between the interfaces, and significantly reduce the interfacial contact thermal resistance, which accounts for the dominant part of the total thermal resistance; the simultaneously increased proportion of dimethicone further reduces the overall rigidity of the system, enhances the wetting effect between the gasket and the contact interface, expands the actual effective heat transfer area, and synergistically reduces the interfacial thermal resistance. In terms of mechanical properties, an appropriate crosslinking density avoids matrix brittleness and interfacial stress concentration caused by excessive crosslinking. The molecular chain segments have better extensibility and stress dispersion ability. Under external load, stress can be uniformly transmitted through chain segment extension, avoiding the brittle fracture defects that are prone to occur in highly crosslinked systems. A higher proportion of dimethicone can fully wet the thermally conductive filler particles, weaken the tendency of filler agglomeration, reduce microscopic defects and stress concentration points inside the system, and make the mechanical load of the crosslinked network more uniform and stable. Ultimately, tensile strength and deformation resistance are simultaneously improved, as obtained from Examples 1-5.

[0052] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the preparation conditions. Based on the data in the table above, it is clear that when preparing high thermal conductivity and low thermal resistance silicon-based composite gel pads, increasing the stirring speed and duration of the curing agent component preparation process, as well as the vulcanization temperature and duration, and the curing temperature, humidity, and duration during the two-stage vulcanization and curing processes, will result in increased thermal conductivity and decreased thermal resistance and mechanical properties of the prepared high thermal conductivity and low thermal resistance silicon-based composite gel pads. The reason for this is that increasing the stirring speed and duration of the curing agent preparation allows for more uniform dispersion of the hydrogen-containing crosslinking agent, inhibitor, and base adhesive, eliminating local component concentration deviations, and resulting in a more even distribution of hydrosilicon addition crosslinking points after subsequent mixing with the base adhesive. First, reducing matrix defects and free volume caused by insufficient local crosslinking reduces phonon scattering loss in the continuous siloxane phase, improving the intrinsic thermal conductivity of the matrix. Second, increasing the temperature and duration of the second-stage vulcanization can promote a more complete hydrosilylation reaction, further improving the density and integrity of the crosslinking network, reducing micropores inside the gasket, increasing overall density, reducing the thermal resistance increase brought by the air phase, strengthening the thermal conductivity pathway in the thickness direction, and optimizing the arrangement of thermally conductive fillers in a high-temperature environment, enhancing the continuity of the multi-scale thermally conductive network, and further improving thermal conductivity. Third, increasing the curing temperature and humidity and extending the curing time can fully relax the residual stress inside the gasket, making the chain segment arrangement more regular, reducing the structural factors that induce phonon scattering, and synergistically improving the overall thermal conductivity. In terms of thermal resistance, the high-temperature treatment of two-stage vulcanization and curing slightly reduces the overall modulus of the gasket, improves the flexibility of the siloxane chain segments, enhances the deformation compliance of the gasket, and allows it to better conform to the microstructure of the contact interface under assembly pressure, effectively eliminating air gaps between interfaces. At the same time, the uniform cross-linked network makes the stress distribution at the interface more balanced, reduces poor contact caused by local high points, and significantly reduces the thermal resistance of the interface contact. In terms of mechanical properties, when the temperature and duration of the second-stage vulcanization exceed the optimal range, excessive cross-linking occurs. The high density of cross-linking points significantly compresses the extensibility of the siloxane molecular chains, reducing chain flexibility and increasing material brittleness. Under external forces, it becomes difficult to disperse stress through chain extension, making brittle fracture more likely. Simultaneously, prolonged high-temperature environments can induce mild thermal oxidation and chain breakage of the siloxane backbone, causing small-molecule silicone oil components to migrate and leak to the surface, weakening the interfacial bonding strength between the matrix and filler. Filler particles are prone to becoming stress concentration points. In addition, the prolonged stress relaxation during the curing stage weakens the physical entanglement between molecular chains. Under the combined effect of multiple factors, the overall mechanical properties of the gasket decrease, as shown in Examples 1 and 6-9.

[0053] Examples 10-27

[0054] The corresponding relationship of the preparation methods used for a high thermal conductivity and low thermal resistance silicon-based composite gel pad is shown in the table below.

[0055] Table: Comparison of the application of high thermal conductivity and low thermal resistance silicon-based composite gel pads in Examples 10-27

[0056] Extract the high thermal conductivity and low thermal resistance silicon-based composite gel pads from Examples 10-27 above, and test their thermal conductivity, interfacial contact thermal resistance and tensile strength according to the above measurement steps and standards. The average value of the test results is recorded in the table below.

[0057] Table: Performance test results of thermal conductivity, interfacial contact thermal resistance and tensile strength in Example 1, 10-27

[0058] As can be seen from the table above, the preparation process of high thermal conductivity and low thermal resistance silicon-based composite gel pads in Examples 1 and 10-27 all effectively improve the production effect of high thermal conductivity and low thermal resistance silicon-based composite gel pads. The base adhesive, as a continuous phase matrix, introduces fluorine units into the main chain to enhance the driving force of fluorine phase migration, providing a carrier for the crosslinking network and thermally conductive filler. The modified thermally conductive filler is the core thermally conductive phase, and the binary particle size distribution is used to increase the packing density, construct a continuous bulk thermally conductive pathway, and improve the characteristic thermal conductivity of the test samples. The hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers in the thermally conductive filler paste are filled with micro-fillers. The filler gaps are widened to build multi-scale phonon bridges, reducing interfacial phonon scattering and further improving the thermal conductivity network. Hydrolyzed silane coupling agent grafts reactive functional groups onto the filler surface, strengthening the interfacial bonding between the filler and siloxane matrix, eliminating interfacial voids, and reducing the filler-matrix interfacial thermal resistance. Vinyl MQ silicone resin participates in the cross-linking reaction, reinforcing the three-dimensional network structure and improving the gasket's resilience and resistance to compression deformation. Methyl phenyl silicone oil adjusts the system viscosity, improving the filler wetting effect and enhancing processing and dispersion uniformity. Liquid fluorosilicone rubber and vinyl fluorosilicone oil, as migratable low-energy components, self-transfer at high temperatures during secondary vulcanization. The surface of the gasket is enriched with a gradient low-energy structure, reducing the gasket's mechanical properties. Pre-dispersed thermally conductive micropowder has pre-embedded thermally conductive pathways within it, maintaining the system's low modulus characteristics, improving interfacial adhesion to reduce contact thermal resistance, and simultaneously avoiding the disruption effect of elasticity on the thermally conductive network. Hydrogen-containing polydimethylsiloxane and fluorinated hydrogen-containing polysiloxane are used as crosslinking agents to construct a complete crosslinked network through hydrosilylation, while the fluorinated crosslinking agent simultaneously replenishes migratable fluorine segments. A platinum catalyst catalyzes the hydrosilylation reaction, regulating the curing reaction rate. A 1-ethynylcyclohexanol inhibitor suppresses catalytic activity at room temperature, enhancing the storage capacity of the two-component system. The polymer exhibits good stability; octamethylcyclotetrasiloxane and dimethylcyclosiloxane form the polymer backbone, providing the intrinsic flexibility and temperature resistance of the siloxane; trifluoropropylmethylcyclotrisiloxane introduces fluorine side chains, endowing the matrix with low mechanical properties; tetramethylammonium hydroxide silanolate catalyzes the ring-opening equilibrium polymerization of cyclosiloxane; tetramethyldivinyldisiloxane acts as a capping agent to regulate the polymer molecular weight and vinyl functionality; methylvinyl silicone rubber raw rubber provides an elastic matrix for the elastic micropowder, supporting the thermally conductive filler and ensuring the flexibility of the micropowder; thus achieving the goal of improving the production effect of high thermal conductivity and low thermal resistance silicone-based composite gel gaskets. Its thermal conductivity is 4-5.2 W / (m·K), which is considered to be high thermal conductivity; the interfacial contact thermal resistance is 0.28-0.4. The thermal resistance is considered low; the mechanical properties of Examples 1, 10, and 12-27 are 1.1-1.48 MPa, which are considered strong mechanical properties; the tensile strength of Example 11 is 0.88 MPa, which is considered average mechanical properties. It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when preparing the base adhesive component, the silicone-based composite gel pad with the strongest thermal conductivity and low thermal resistance obtained using 100 parts of base adhesive, 14 parts of vinyl MQ silicone resin, 12 parts of methyl phenyl silicone oil, 5 parts of liquid fluorosilicone rubber, 6 parts of pre-dispersed thermally conductive micropowder, 4 parts of vinyl fluorosilicone oil, 72 parts of thermally conductive filler paste, 232 parts of modified thermally conductive filler, and 1 part of platinum catalyst exhibits the most robust thermal conductivity and mechanical properties. This is attributed to the significantly increased total thermally conductive filler content, where binary spherical alumina particles create a continuous and dense micron-level thermal conductivity structure. The framework, with hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers filling the gaps between particles, constructs a multi-scale phonon transport bridge, significantly increasing the proportion of thermally conductive phase and the packing density per unit volume. This reduces the blocking and interruption effects of low thermal conductivity siloxane protons on the heat transfer pathway, effectively enhancing the heat conduction efficiency in the thickness direction. The simultaneous increase in the amount of vinyl MQ silicone resin and platinum catalyst promotes a more complete hydrosilylation reaction, further enhancing the density and uniformity of the crosslinked network. The silane coupling agent-modified filler has a stronger interface with the matrix, significantly reducing interfacial voids and phonon scattering losses. At the same time, the high degree of crosslinking compresses the free volume of the matrix, reducing phonon scattering caused by chain segment defects, synergistically promoting optimal thermal conductivity. In terms of mechanical properties, vinyl MQ silicone resin, as a rigid reinforcing component, can directly participate in the crosslinking reaction, introducing a high-hardness resin phase into the three-dimensional network. The higher proportion significantly improves the cohesive strength and resistance to compressive deformation of the crosslinking system. The high-filler thermally conductive filler forms a dense particle-bearing skeleton inside the system. Combined with the interfacial chemical bonding effect of the silane coupling agent, the filler and siloxane matrix form a strong bonding interface. Under external force, stress can be uniformly transferred and dispersed through the filler skeleton, avoiding fracture failure caused by local stress concentration. The increased amount of platinum catalyst makes the crosslinking reaction more complete, the crosslinking point distribution more uniform, and the chemical connection between molecular chains more compact, effectively improving the tensile strength and tear resistance of the system. The pre-dispersed thermally conductive micropowder and a small amount of fluorine-containing components can moderately buffer the interfacial stress and alleviate the brittleness tendency of the high-filler system, maintaining a certain toughness while ensuring high strength, as obtained from Examples 1 and 10-13.

[0059] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when preparing the base adhesive component, the silicone-based composite gel pad with the lowest thermal resistance was prepared using 100 parts base adhesive, 8 parts vinyl MQ silicone resin, 22 parts methyl phenyl silicone oil, 5 parts liquid fluorosilicone rubber, 12 parts pre-dispersed thermally conductive micropowder, 4 parts vinyl fluorosilicone oil, 45 parts thermally conductive filler paste, 190 parts modified thermally conductive filler, and 0.8 parts platinum catalyst. This is because reducing the reinforcing proportion of vinyl MQ resin and the total amount of thermally conductive filler, increasing the amount of methyl phenyl silicone oil and pre-dispersed thermally conductive elastic micropowder, and simultaneously reducing the amount of catalyst... The cross-linking density of the system significantly reduces the overall modulus and hardness of the gasket; the lower material rigidity gives the gasket better deformation compliance, and under normal assembly pressure, it can fully fill the micro-uneven morphology of the heat dissipation interface, effectively eliminate air gaps between interfaces, and significantly reduce the interfacial contact thermal resistance, which accounts for the majority of the total thermal resistance; the more flexible elastic micro powder and the higher proportion of phenyl silicone oil can optimize the stress distribution of the system, alleviate the interfacial stress between the filler and the matrix, reduce phonon scattering loss at the interface, and offset the weakening effect of the bulk thermal conductivity caused by the reduction in filler content; the sparser cross-linking network increases the degree of freedom of movement of the siloxane chain segments, enhances the wetting effect between the gasket and the contact interface, expands the actual effective heat transfer area, and thus reduces thermal resistance, as obtained from Examples 1 and 10-13.

[0060] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the preparation conditions. Based on the data in the table above, it is clear that when preparing the base adhesive component, increasing the temperature, rotation speed, and time of the modified thermally conductive filler process; and increasing the reaction temperature and equilibrium reaction time of the ring-opening polymerization process; will result in improved thermal conductivity and mechanical properties, and decreased thermal resistance, of the prepared high thermal conductivity and low thermal resistance silicon-based composite gel pads. The reason for this is that increasing the pre-dispersion temperature, rotation speed, and heat preservation modification time of the modified thermally conductive filler process allows for silane coupling. The grafting reaction of the agent on the surface of spherical alumina is more complete and uniform, forming a continuous and dense coupling agent coating layer on the filler surface. This effectively weakens the polarity of the filler surface and the driving force for interparticle agglomeration, enhances the interfacial wettability and chemical bonding strength between the filler and the siloxane matrix, and reduces the microscopic voids and phonon scattering loss at the filler-matrix interface, providing a solid interfacial foundation for the continuous construction of multi-scale thermal conductivity networks. Higher dispersion speed and longer heat preservation modification time can fully break down the soft agglomerates of the filler, making the binary particle size alumina filler more uniformly dispersed during subsequent kneading and mixing, and the thermal conductivity pathways more evenly distributed. The continuous and dense structure not only improves the intrinsic thermal conductivity of the gasket but also reduces internal micropores and air content, thereby lowering the bulk thermal resistance. The increased interfacial bonding strength between the filler and the matrix allows for efficient transfer of external loads to the inorganic filler skeleton through interfacial chemical bonds, fully leveraging the load-bearing and reinforcing role of the rigid filler. Simultaneously, the uniform filler dispersion eliminates stress concentration defects caused by localized agglomeration, preventing brittle fracture at agglomeration points under stress and simultaneously improving the tensile strength and deformation resistance of the system. Increasing the reaction temperature and equilibrium reaction time of the ring-opening polymerization process facilitates the ring-opening polymerization of cyclosiloxane monomers. The reaction is more complete, the polymer molecular chain length increases and the molecular weight distribution is narrower, the regularity of the main chain structure is significantly improved, the chain end defects and disordered segments in the siloxane are reduced, the scattering loss of phonons in the continuous phase is reduced, and the intrinsic thermal conductivity of the matrix is ​​improved. At the same time, the more uniform distribution of vinyl functional groups makes the crosslinking points of subsequent hydrosilylation more uniform, reducing the structural defects caused by insufficient or excessive crosslinking in some areas. The mechanical load-bearing capacity of the crosslinking network is more balanced and stable. The physical entanglement between long molecular chains and the chemical crosslinking points work together to effectively improve the overall mechanical strength and tear resistance of the gasket. In terms of thermal resistance, the well-structured and uniformly performing polymer matrix, combined with the uniformly dispersed thermally conductive filler, makes the overall modulus distribution of the gasket consistent and the surface flatness improved. Under assembly pressure, it can fully conform to the micro-concavity and convexity of the contact interface, effectively eliminating air gaps between interfaces and significantly reducing interfacial contact thermal resistance. The improvement of the intrinsic thermal conductivity of the matrix and the reduction of interfacial contact thermal resistance form a synergistic effect, jointly promoting the continuous reduction of the total thermal resistance of the gasket, as obtained in Examples 1 and 14-19.

[0061] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the preparation conditions. Based on the data in the table above, it is clear that increasing the plate vulcanization temperature and vulcanization time during the preparation of the base adhesive component leads to improvements in the thermal conductivity, mechanical properties, and thermal resistance of the resulting high thermal conductivity and low thermal resistance silicon-based composite gel pads. This is because increasing the plate vulcanization temperature and extending the vulcanization time allows for a more complete and thorough hydrosilicon crosslinking reaction within the pre-dispersed thermally conductive micropowder. The cross-linking density of the micropowder itself is significantly improved, and the internal three-dimensional network structure is more compact and orderly. The spherical alumina filler embedded in the micropowder is more stably and orderly arranged, reducing the chain segment defects and free volume of the elastic matrix inside the micropowder, reducing the scattering loss of phonons in the micropowder phase, and improving the thermal conductivity of the micropowder itself. After the micropowder is added to the overall matrix, it can reduce the interruption effect of low thermal conductivity elasticity relative to the overall thermal conductive network, and form a smoother heat transfer connection with the surrounding micron thermal conductive filler, thereby promoting the improvement of the intrinsic thermal conductivity of the gasket as a whole. The pre-dispersed thermal conductive micropowder is subjected to higher temperatures and more After prolonged vulcanization, the cohesive strength and rigidity of the gasket are significantly enhanced, forming rigid elastic micro-regions with a certain load-bearing capacity. These micro-regions, uniformly dispersed within the siloxane matrix, act as rigid particle reinforcements. Under external loads, the highly cross-linked micropowder effectively transfers and disperses stress, inhibiting crack propagation. Simultaneously, the surface layer of the micropowder forms chemical bonds with the matrix cross-linked network, improving interfacial bonding strength and preventing interfacial debonding failure under stress. Ultimately, this leads to a simultaneous increase in the overall tensile strength and deformation resistance of the gasket, resulting in enhanced mechanical properties. Despite the thermal conductivity of the micropowder itself... While increasing the degree of vulcanization can slightly reduce the thermal resistance of the gasket, it can also significantly increase the hardness and modulus of the micropowder itself, weakening its flexible deformation ability. After being added to the matrix, the overall rigidity of the gasket increases and the interface conformability decreases. Under the same assembly pressure, the gasket cannot fully fill the micro-uneven morphology of the heat dissipation interface, resulting in more residual air gaps between the interfaces. The interfacial contact thermal resistance, which dominates the total thermal resistance, increases significantly, and its increase exceeds the decrease in the thermal resistance of the gasket. Ultimately, this leads to an increase in the total thermal resistance of the gasket, as shown in Examples 1 and 14-19.

[0062] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the proportions of the raw materials. Based on the data in the table above, it is clear that when the modified thermally conductive filler is prepared using spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and silane coupling agent hydrolysate at a mass ratio of 2:8:0.18, the resulting silicon-based composite gel pad exhibits the strongest thermal conductivity and low thermal resistance. This is because this formulation increases the proportion of large-particle-size spherical alumina to form a binary close-packed system. Large particles build a continuous, dominant thermal framework, while small particles fill the gaps. The interparticle gaps significantly improve the overall packing density and the proportion of thermally conductive phase per unit volume of the filler, reducing the obstruction of heat transfer pathways by low thermal conductivity siloxane alkyl bodies and enhancing heat conduction efficiency in the thickness direction. The increased proportion of large-diameter particles reduces the total specific surface area of ​​the filler, and the amount of silane coupling agent is reduced accordingly to avoid the formation of a weak bonding layer at the interface by excessive coupling agent, reducing phonon scattering loss at the filler-matrix interface and ensuring efficient heat transfer at the solid-solid interface. The higher packing density compresses the air micropores inside the gasket, eliminating the obstruction of heat transfer by low thermal conductivity air, and further improving the overall thermal conductivity of the gasket, as obtained from Examples 1 and 20-21.

[0063] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the proportions of the raw materials. Based on the data in the table above, it is clear that when the modified thermally conductive filler is prepared using spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and silane coupling agent hydrolysate in a mass ratio of 4:6:0.25, the resulting high thermal conductivity and low thermal resistance silicon-based composite gel pad exhibits the lowest thermal resistance and the strongest mechanical properties. This is because, under this ratio, the proportion of small-particle-size spherical alumina increases, leading to a larger total specific surface area of ​​the filler. The simultaneously increased amount of silane coupling agent can form a complete and continuous graft coating layer on the filler surface, strengthening the interfacial bonding strength between the filler and the siloxane matrix, eliminating microscopic voids at the filler-matrix interface, and reducing interfacial... Surface phonon scattering reduces interfacial thermal resistance; finer filler particles fully fill the gaps between large particles, making the internal filler arrangement of the gasket more dense and delicate, reducing internal micropores and air content, while improving the surface flatness of the gasket, enabling more complete interfacial adhesion under assembly pressure, effectively eliminating air gaps between interfaces, and significantly reducing interfacial contact thermal resistance; small-diameter fillers and appropriate amounts of coupling agents synergistically enhance the chemical bonding between the filler and the matrix interface, efficiently transferring stress through the interface under external loads, and fully utilizing the load-bearing and reinforcing effect of inorganic fillers; the dense filler arrangement reduces agglomeration defects and stress concentration points within the system, and the mechanical load-bearing capacity of the cross-linked network is more uniform and stable, effectively inhibiting crack initiation and propagation, ultimately achieving the optimal level of overall mechanical strength of the gasket, as obtained from Examples 1 and 20-21.

[0064] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when the base adhesive component is prepared using a thermally conductive filler paste composed of hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 31.5:4.5:0.9:12.6:2.89, the resulting high thermal conductivity and low thermal resistance silicon-based composite gel pad exhibits the strongest thermal conductivity and mechanical properties. This is because this ratio increases the relative proportion of hexagonal boron nitride nanosheets and reduces the total proportion of silicone oil, effectively increasing the solid content and density of the two-dimensional thermally conductive filler paste. The two-dimensional boron nitride nanosheets can build continuous in-plane phonons within the micron-sized filler gaps. The transmission channel opens up the heat transfer breakpoints between adjacent heat-conducting particles, reducing phonon scattering loss at the interface. The lower silicone oil content reduces the obstruction and dilution effect of low thermal conductivity oil relative to the heat conduction path, resulting in a higher proportion of heat-conducting phase per unit volume and a more continuous and dense overall heat conduction path, significantly improving the thermal conductivity of the gasket. The high proportion of two-dimensional boron nitride nanosheets has excellent layer reinforcement effect. When uniformly dispersed in siloxane matrix, it can effectively transfer external loads and hinder crack propagation. With an appropriate amount of silane coupling agent, it can strengthen the interfacial bonding strength between the filler and the matrix, avoiding interfacial debonding failure during stress. The appropriate amount of silicone oil component ensures the wetting and dispersion effect of the filler without excessively softening the cross-linked matrix, keeping the cohesive strength of the cross-linked network of the system at a high level, as obtained from Examples 1 and 22-23.

[0065] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when the thermally conductive filler paste used in the preparation of the base adhesive component is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 28.8:7.2:1.08:16.2:4.32, the resulting high thermal conductivity and low thermal resistance silicon-based composite gel pads are significantly improved. The lowest thermal resistance is attributed to the formulation's increased proportion of silicon carbide whiskers and simultaneous increase in the total amount of silane coupling agent and silicone oil, which enhances the filler interface coating and dispersion effect. More silicon carbide whiskers can refine the filling gaps, alleviate the stress at the filler-matrix interface, and reduce interfacial phonon scattering loss. The higher proportion of silicone oil reduces the overall modulus of the system, improves the gasket's deformation compliance, and can fully conform to the interface microstructure under assembly pressure, eliminating air gaps and effectively reducing interfacial contact thermal resistance, as obtained in Examples 1 and 22-23.

[0066] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel pads can be increased by adjusting the proportions of the raw materials. Based on the data in the table above, it is clear that when the base adhesive is prepared using octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 72:24:4:0.05:0.6, the resulting high thermal conductivity and low thermal resistance silicon-based composite gel pad exhibits the strongest thermal conductivity and mechanical properties. This is because this ratio reduces the proportion of fluorine monomers and the amount of end-capping agent, resulting in a polymer matrix with higher molecular weight and more regular chain structure. The longer molecular chains reduce chain end defects and free radicals. The increased volume reduces phonon scattering loss in the siloxane matrix, improving the intrinsic thermal conductivity of the matrix. Higher matrix viscosity and mechanical load-bearing capacity allow for higher filler content, ensuring uniform filler dispersion and structural stability of the thermally conductive network, further enhancing the overall thermal conductivity of the gasket. The significantly enhanced physical entanglement between long molecular chains, combined with uniformly distributed vinyl functional groups, makes the crosslinking points of the subsequent crosslinking network more uniform. The cohesive strength and deformation resistance of the crosslinking system are simultaneously improved. Under external force, the molecular chains can evenly disperse stress through orderly extension, avoiding fracture failure caused by localized stress concentration. Simultaneously, the regular chain segment structure strengthens the interfacial bonding between the matrix and the filler, fully utilizing the load-bearing and reinforcing role of the inorganic filler, as obtained in Examples 1 and 24-25.

[0067] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicon-based composite gel gaskets can be increased by adjusting the proportions of these materials. Based on the data in the table above, it is clear that when the base adhesive is prepared using octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 65:22:13:0.05:0.75, the resulting high thermal conductivity and low thermal resistance silicon-based composite gel gasket exhibits the lowest thermal resistance. This is because this ratio increases the proportion of trifluoropropylcyclosiloxane, imparting a lower intrinsic surface energy to the polymer matrix, resulting in a lower thermal resistance at the gasket-contact interface. The wettability is significantly improved, effectively expanding the actual effective heat transfer area and reducing phonon reflection loss at the interface. The amount of end-capping agent is simultaneously increased to control the polymer molecular weight to a suitable range. Combined with the internal plasticizing effect of fluorine side chains, the siloxane molecular chains maintain excellent flexibility. After cross-linking and molding, the overall modulus of the gasket is moderate, and the deformation compliance is good. Under assembly pressure, it can fully conform to the micro-uneven morphology of the contact interface, effectively eliminating residual air gaps between interfaces and significantly reducing the interfacial contact thermal resistance, which accounts for the majority of the total thermal resistance. The uniformly distributed fluorine side chains can optimize the interfacial bonding state between the matrix and the thermally conductive filler, reduce the micro-voids and phonon scattering at the filler interface, and further reduce the interfacial thermal resistance, as obtained from Examples 1 and 24-25.

[0068] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel pads can be increased by adjusting the proportions of the raw materials. Based on the data in the table above, it is clear that when the pre-dispersed thermally conductive micropowder is prepared from methyl vinyl silicone rubber raw material, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and a pre-diluted complex in a mass ratio of 100:90:1.7:0.10, the resulting high thermal conductivity and low thermal resistance silicone-based composite gel pad exhibits the strongest thermal conductivity and mechanical properties. This is because this ratio significantly increases the proportion of spherical alumina filler, creating a more continuous and dense thermally conductive pathway within the micropowder. The higher filler density also reduces the relative thermal conductivity of the elastic matrix. The network interruption effect allows the micropowder to form a smoother heat transfer connection with the surrounding micron fillers after being added to the overall system, reducing the scattering loss of phonons in the elastic phase and significantly improving the overall thermal conductivity of the gasket. The simultaneously increased amount of crosslinking agent and catalyst makes the silane crosslinking reaction inside the micropowder more complete and thorough, significantly improving the crosslinking density and cohesive strength of the micropowder itself, forming a rigid elastic micro-region with high load-bearing capacity. The uniform dispersion in the siloxane matrix can effectively transfer and disperse external loads and inhibit crack propagation. At the same time, the surface layer of the micropowder can form chemical bonds with the matrix crosslinking network, with excellent interfacial bonding strength, giving full play to the micro-region reinforcement effect and synergistically improving the overall mechanical strength of the gasket, as obtained from Examples 1 and 26-27.

[0069] It is evident that, given a fixed amount of raw materials, the production efficiency of high thermal conductivity and low thermal resistance silicone-based composite gel gaskets can be increased by adjusting the proportions of the raw materials. Based on the data in the table above, it is clear that when the base adhesive component is prepared using pre-dispersed thermally conductive micropowder composed of methyl vinyl silicone rubber raw rubber, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and pre-diluted complex in a mass ratio of 100:40:1.2:0.06, the resulting high thermal conductivity and low thermal resistance silicone-based composite gel gasket exhibits the lowest thermal resistance. This is attributed to the reduced amount of thermally conductive filler and crosslinking agent in this formulation, which lowers the crosslinking density and rigidity of the micropowder itself. The more flexible elastic micropowder significantly reduces the overall modulus of the gasket, improves material deformation compliance, and fully fills the microscopic unevenness of the interface under assembly pressure, eliminating air gaps and drastically reducing interfacial contact thermal resistance. The high elasticity of the micropowder buffers interfacial stress, optimizes the contact state of the heat transfer interface, and achieves the lowest possible overall thermal resistance, as obtained in Examples 1 and 26-27.

[0070] This specific embodiment is merely an explanation of the present invention and not a limitation thereof. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of the claims of the present invention, they are protected by patent law.

Claims

1. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance, characterized in that, The raw materials for preparing the high thermal conductivity and low thermal resistance silicon-based composite gel pad, by weight, include: 9-15 parts of hydrogen-containing polydimethylsiloxane, 3-7 parts of fluorinated hydrogen-containing polysiloxane, 59-73 parts of dimethicone oil, 15-25 parts of base adhesive, 0.15-0.2 parts of 1-ethynylcyclohexanol inhibitor, and 1000 parts of base adhesive components.

2. The silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 1, characterized in that: The preparation method of the base adhesive component includes the following steps: C1. Spherical alumina with an average particle size of 5 μm and spherical alumina with an average particle size of 40 μm were mixed and put into a high-speed mixer. 1.5 times the volume of ethanol-water mixture was added, and the mixture was stirred at 200 r / min to form a uniform suspension. The pH of the system was adjusted to 4.5-5.0 with glacial acetic acid. Then, silane coupling agent hydrolysate was added dropwise for 1 h. The mixture was stirred at 60-70℃ and 300-500 r / min for 2.5-3.5 h. After the reaction was completed, the mixture was centrifuged, washed twice with anhydrous ethanol, and dried in a 105℃ forced-air drying oven for 2 h to obtain the modified thermally conductive filler. C2. Hydroxylated hexagonal boron nitride nanosheets and silicon carbide whiskers were added to a high-speed dispersion vessel, along with silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil. The mixture was then sheared and dispersed at 3000 r / min for 20 min. The mixture was then transferred to a vacuum degassing vessel and depressurized at room temperature and -0.095 MPa for 15 min. The slurry was then transferred to a three-roll mill, with the roller speed ratio controlled at 1:1.2:1.5 and the roller spacing gradually reduced from 40 μm to 20 μm. The mixture was then repeatedly ground twice using a light grinding process to obtain a thermally conductive filler paste. C3. Octamethylcyclotetrasiloxane, dimethylcyclosiloxane, and trifluoropropylmethylcyclotrisiloxane are added to a polymerization reactor. Nitrogen gas is introduced to replace the air in the reactor. Tetramethylammonium hydroxide silanolate catalyst and tetramethyldivinyldisiloxane end-capping agent are added. The mixture is stirred at 105-115℃ and 70-90 r / min for 3.5-4.5 h until ring-opening equilibrium is reached. The temperature is first increased to 130℃ at a gradient rate of 2℃ / min and held for 1 h to decompose the catalyst. The temperature is then increased to 150℃. Low-boiling substances are first pre-removed under a vacuum of -0.05MPa for 30 min. The vacuum is then gradually increased to -0.095MPa and maintained for 2 h. A small amount of nitrogen gas is introduced throughout the process. After the devolatilization is completed, heating is stopped, and the mixture is cooled to room temperature and discharged to obtain the base adhesive. C4. Raw methyl vinyl silicone rubber and spherical alumina with an average particle size of 5μm are fed into a two-roll mill. The roller temperature is controlled at ≤40℃. The mixture is kneaded until the powder is completely coated with the rubber. The material is discharged and cooled to room temperature. The cooled masterbatch is fed back into the two-roll mill. Hydrogen-containing silicone oil is added. The mixture is passed through a thin pass twice and then a pre-diluted complex is added. The mixture is passed through a thin pass twice more until the system is homogeneous. The material is immediately discharged and placed in a flat vulcanizing machine. It is hot-pressed and vulcanized at 95-105℃ for 3-8 minutes to produce a sheet with a thickness of 0.5mm. After being embrittled by liquid nitrogen freezing, the sheet is fed into a pulverizer and pulverized. The powder with an average particle size of 20μm is selected by airflow sieving to obtain pre-dispersed thermally conductive powder. C5. The base adhesive obtained from C3, vinyl MQ silicone resin, methyl phenyl silicone oil, liquid fluorosilicone rubber, pre-dispersed thermally conductive micropowder obtained from C4, and vinyl fluorosilicone oil are added to a kneader and premixed at room temperature and speed of 60 r / min for 30 min. The thermally conductive filler paste obtained from C2 is added in 3 portions, and the temperature is raised to 100℃ after each addition, and kneaded at speed of 80 r / min for 20 min. The modified thermally conductive filler obtained from C1 is added in 4 portions, and kneaded under vacuum of -0.095 MPa for 25 min after each addition. After kneading, the mixture is cooled to room temperature, a platinum catalyst is added, and the mixture is stirred at low speed for 15 min. Vacuum degassing is performed until no bubbles overflow, and the base adhesive component is obtained.

3. The silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 1, characterized in that: The raw materials for preparing the base adhesive component and their weight proportions are as follows: 100 parts base adhesive, 8-18 parts vinyl MQ silicone resin, 10-22 parts methyl phenyl silicone oil, 5-12 parts liquid fluorosilicone rubber, 6-15 parts pre-dispersed thermally conductive micro powder, 4-9 parts vinyl fluorosilicone oil, 45-72 parts thermally conductive filler paste, 190-232 parts modified thermally conductive filler, and 0.8-1 parts platinum catalyst.

4. The silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The silane coupling agent hydrolysate is obtained by mixing vinyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, anhydrous ethanol, and deionized water in a mass ratio of 6:2:1.5:0.

5.

5. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The modified thermally conductive filler is prepared by mixing spherical alumina with an average particle size of 5 μm, spherical alumina with an average particle size of 40 μm, and hydrolysate of silane coupling agent in a mass ratio of 2-4:6-8:0.18-2.

25.

6. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The thermally conductive filler paste is prepared from hydroxylated hexagonal boron nitride nanosheets, silicon carbide whiskers, silane coupling agent hydrolysate, dimethyl silicone oil, and methylphenyl silicone oil in a mass ratio of 28.8-31.5:4.5-7.2:0.9-1.08:12.6-16.2:2.89-4.

32.

7. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The base adhesive is prepared from octamethylcyclotetrasiloxane, dimethylcyclosiloxane, trifluoropropylmethylcyclotrisiloxane, tetramethylammonium hydroxide silanolate catalyst, and tetramethyldivinyldisiloxane end-capping agent in a mass ratio of 65-72:22-24:4-13:0.05:0.6-0.

75.

8. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The pre-dispersed thermally conductive micropowder is prepared from methyl vinyl silicone rubber raw rubber, spherical alumina with an average particle size of 5 μm, hydrogen-containing silicone oil, and pre-diluted complex in a mass ratio of 100:40-90:1.2-1.7:0.06-0.

1.

9. A silicon-based composite gel pad with high thermal conductivity and low thermal resistance according to claim 2, characterized in that: The pre-diluted complex was obtained by diluting a platinum-divinyltetramethyldisiloxane complex with a base adhesive obtained from C3 at a mass ratio of 10:

1.

10. A method for preparing a high thermal conductivity, low thermal resistance silicon-based composite gel pad according to any one of claims 1-9, characterized in that, The method for preparing the high thermal conductivity and low thermal resistance silicon-based composite gel pad includes the following steps: S1. Add hydrogen-containing polydimethylsiloxane, fluorinated hydrogen-containing polysiloxane, dimethyl silicone oil, and base adhesive to a mixing tank, add 1-ethynylcyclohexanol inhibitor, stir at room temperature and speed of 70-110 r / min for 20-30 min, and then degas at -0.09 MPa vacuum for 10 min to obtain curing agent components. S2. The base adhesive component and the curing agent component obtained in S1 are fed into a mixer and thoroughly mixed at a flow rate of 5 L / min. The mixture is then coated onto the surface of a microporous fluorine release film using a coating machine. The coating back pressure is controlled to be ≤0.2 MPa, and the coating thickness is 1.0 mm. The adhesive surface is covered with the same microporous fluorine release film. The release film is continuously fed into a tunnel-type drying tunnel. The temperature of the first section of the drying tunnel is 95℃, and the dwell time is 10 min to complete the initial setting of the adhesive. The temperature of the second section of the drying tunnel is 125℃, and the dwell time is 15 min to complete the main cross-linking reaction. After exiting the drying tunnel, the mixture is naturally cooled to room temperature and then wound up to obtain a pre-cured gel sheet. S3. Peel off the upper and lower release films from the pre-cured gel sheet obtained in S2, lay it flat on the breathable mesh belt, transfer it into a nitrogen-filled drying oven, control the oxygen content in the oven to be below 500ppm, and carry out a two-stage vulcanization treatment at 150-160℃ for 2-3 hours. After naturally cooling to room temperature, transfer it to a constant temperature and humidity environment at 20-30℃ and 45-55% for 8-16 hours of static curing. Trim and trim the edges to obtain a high thermal conductivity and low thermal resistance silicon-based composite gel pad.